2001
DOI: 10.1038/35105060
|View full text |Cite
|
Sign up to set email alerts
|

The function of E- and id proteins in lymphocyte development

Abstract: Helix-loop-helix proteins are essential factors for lymphocyte development and function. In particular, E-proteins are crucial for commitment of lymphoid progenitors to the B- and T-cell lineages. E-proteins are negatively regulated by the Id class of helix-loop-helix proteins. The Id proteins function as dominant-negative inhibitors of E-proteins by inhibiting their ability to bind DNA. Here, we review the role of E-proteins and their Id protein antagonists in lymphocyte proliferation and developmental progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(183 citation statements)
references
References 68 publications
2
170
1
10
Order By: Relevance
“…This Tax-induced E2A protein silencing mechanism is reminiscent of that associated with the AML-ETO fusion protein that inhibits transcriptional activation by E proteins through stable interactions that preclude recruitment of the coactivators (47). This mechanism is therefore fundamentally distinct from that used by Id proteins which, through interactions with DNA binding regions of E2A proteins, block binding to the promoter (11,12). During early thymocyte development, the E2A proteins function as gatekeepers to arrest both differentiation and proliferation of thymocytes with defects in the assembly of the pre-TCR complex.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This Tax-induced E2A protein silencing mechanism is reminiscent of that associated with the AML-ETO fusion protein that inhibits transcriptional activation by E proteins through stable interactions that preclude recruitment of the coactivators (47). This mechanism is therefore fundamentally distinct from that used by Id proteins which, through interactions with DNA binding regions of E2A proteins, block binding to the promoter (11,12). During early thymocyte development, the E2A proteins function as gatekeepers to arrest both differentiation and proliferation of thymocytes with defects in the assembly of the pre-TCR complex.…”
Section: Discussionmentioning
confidence: 94%
“…Before reverse transcription, RNAs were first treated with 10 U of RNase-free DNase I (QIAGEN) for 30 min at 27°C and then for 10 min at 60°C. This RNA sample was then reverse transcribed at 42°C for 1 h in a total volume of 20 l reaction buffer (50 mM Tris, pH 8.3, 30 mM KCl, 3 mM MgCl 2 , 10 mM dithiothreitol) containing 100 U of SuperScriptII RNase H Ϫ reverse transcriptase (RT; Invitrogen), 100 pmol of oligo(dT) [12][13][14][15][16][17][18] (Invitrogen), and 20 U of RNase inhibitor (Rnasin; Promega). A reaction without RT was performed in parallel to serve as control for the absence of DNA contamination.…”
Section: Cells and Plasmidsmentioning
confidence: 99%
“…Id proteins are known to negatively regulate another class of HLH proteins, the E-proteins, by inhibiting these proteins' ability to bind DNA. The E-proteins play crucial roles in survival, proliferation and differentiation of lymphocytes, and interestingly, they have been shown to both promote and inhibit growth at different stages of lymphocyte development [9,10]. It has been shown that T cell development is partially blocked at the CD4 -CD8 -double-negative 1 stage in E2A-deficient mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed toward members of the inhibitor of DNA binding (Id) protein family, a class of helix-loop-helix (HLH) proteins, as important targets for BMP signalling [5][6][7][8]. HLH proteins act as transcriptional regulators and are essential factors for lymphoid development and function [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also highlighted their role in cellular senescence (3,4) and in cell fate decisions in cells of specialized lineages such as lymphocytes (5) (reviewed in Ref. 6), vascular endothelial cells (7,8), and neuronal cells (7,9). The four members of the Id protein family (Id1-Id4) function by directly associating with and modulating the activity of several families of transcriptional regulators (1, 10 -12).…”
mentioning
confidence: 99%